Dualism Wave-Particle and the Value of the Scientific Theory in Bohr. The Necessary Consideration of Materialist Dialectics - Henriques Pato, Ana (Revista de Humanidades de Valparaíso, 2014)
In the XXth century, the development of science has posed new challenges to the physicists. Waves have exhibited a corpuscular behavior while particles have exhibited undulatory behavior, but never simultaneously. This difficulty led Bohr to adopt the principle of complementarity, the figure by which the contradiction between wave and corpuscle is fixed. Thus the opposition between wave and corpuscle is absolutized. I think it was the non-consideration of dialectics that prevented Bohr from advancing towards the resolution of that objective contradiction, that was about to be reflected on the theory. Consequently, it is the objective reality, in its unity and as a contradictory totality, that is removed from the theory. The scientific theory gives up the search for the internal connection of phenomena and its task becomes the mere ordination of such phenomena. The repression of the internal contradiction of reality has a second consequence in Bohr’s thought: objectivity becomes internal to language and it is considered under the figure of intersubjectivity. In fact, Bohr, by puting the correlation between object and measuring instrument (by making the phenomenon dependent of the experience, of the human practice) as the instance in which knowledge is founded, is denying the possibility that there is a content of human representations that does not depend on the subject, i.e. is denying the possibility of objectivity. These are the general guidelines on which I will argue.